2020
DOI: 10.1093/ecco-jcc/jjaa233
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for the Treatment of Ulcerative Colitis: Analysis of Infection Rates from the Ulcerative Colitis Clinical Programme

Abstract: Background and Aims Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis. We report integrated analyses of infections in the Phase [P]2 and P3 OCTAVE programmes. Methods Three cohorts were analysed: Induction [P2/3 induction studies]; Maintenance [P3 maintenance study]; and Overall [all tofacitinib-treated patients in induction, maintenance or ongoing, open-label, long-term extension st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 54 publications
10
36
0
Order By: Relevance
“…[20][21][22][23][24] In a recent meta-analysis of the real-world effectiveness and safety of tofacitinib for moderate to severely active UC, which included data from 1162 patients in 17 studies, the herpes zoster IR was reported to be 6.9 (95% CI, 4.5-9.3), 25 which is higher than the herpes zoster 25 Prior failure of biologic therapy is a known risk factor for herpes zoster in patients with UC. 26 In addition, with the exception of a higher IR for herpes zoster, the safety of tofacitinib in OCTAVE Open was similar to that reported for other approved UC therapies, including biologics. 27 The IRs of adverse events of special The safety profile of tofacitinib in OCTAVE Open was consistent with previously published long-term studies of tofacitinib in patients with rheumatoid arthritis, active psoriatic arthritis or moderate to severe chronic plaque psoriasis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…[20][21][22][23][24] In a recent meta-analysis of the real-world effectiveness and safety of tofacitinib for moderate to severely active UC, which included data from 1162 patients in 17 studies, the herpes zoster IR was reported to be 6.9 (95% CI, 4.5-9.3), 25 which is higher than the herpes zoster 25 Prior failure of biologic therapy is a known risk factor for herpes zoster in patients with UC. 26 In addition, with the exception of a higher IR for herpes zoster, the safety of tofacitinib in OCTAVE Open was similar to that reported for other approved UC therapies, including biologics. 27 The IRs of adverse events of special The safety profile of tofacitinib in OCTAVE Open was consistent with previously published long-term studies of tofacitinib in patients with rheumatoid arthritis, active psoriatic arthritis or moderate to severe chronic plaque psoriasis.…”
Section: Discussionsupporting
confidence: 64%
“…Of note, however, patients receiving tofacitinib in the real‐world settings described in this meta‐analysis had a higher rate of failure of biologic therapy, with nearly 90% of patients having prior biologic exposure and approximately two‐thirds having prior TNFi and vedolizumab failure, versus almost half of patients in the OCTAVE studies being naïve to biologic therapy 25 . Prior failure of biologic therapy is a known risk factor for herpes zoster in patients with UC 26 . In addition, with the exception of a higher IR for herpes zoster, the safety of tofacitinib in OCTAVE Open was similar to that reported for other approved UC therapies, including biologics 27 .…”
Section: Discussionmentioning
confidence: 90%
“…10 In the PMS data from patients with UC, the most frequently reported infections were nasopharyngitis and herpes zoster, which is consistent with infection AEs reported in tofacitinib clinical trials. 13 Compared with the general population, patients with inflammatory bowel disease are at increased risk of herpes zoster, 8 and this risk is increased further by treatment with immunosuppressive therapies. 14 Consistent with herpes zoster events reported in tofacitinib clinical trials, 13 the majority of herpes zoster infections in the PMS dataset were categorised as not serious.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared with the general population, patients with inflammatory bowel disease are at increased risk of herpes zoster, 8 and this risk is increased further by treatment with immunosuppressive therapies. 14 Consistent with herpes zoster events reported in tofacitinib clinical trials, 13 the majority of herpes zoster infections in the PMS dataset were categorised as not serious.…”
Section: Discussionmentioning
confidence: 99%
“…In the OCTAVE trials, nearly half of patients were anti‐TNF‐naïve and prior treatment with vedolizumab was not allowed 2 . In the integrated analyses of infections throughout the global tofacitinib UC clinical programme, prior failure to anti‐TNF was a significant risk factor for herpes zoster (HR 1.76, 95% CI 1.13‐2.74] 9 . Remarkably, none of the real‐world studies included in the review reported major adverse cardiovascular events or thromboembolic complications 8 .…”
mentioning
confidence: 99%